Environmental Management System of Petroleum Industries: A case study of Oil and Gas Exploration in the Zamrud Field Conservation Areas - Setiani, Onny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACT Background:The Zamrud Field is one of the oil fields managed by Caltex Pacific Indonesia (CPI) a production sharing contractor of Pertamina. It is located in the Coastal Plain and Pekanbaru (CPP) Block. The government of Indonesia has designated Zamrud as a conservation area. The petroleum industry in Zamrud fields has received 14001 ISO Certificate on Environmental Management System. The production sharing contract between CPI and the Government of Indonesia expired in August 2002 Methods: .This case study describes how CPI managed the development of oil and gas production and compared to the environmental management system for petroleum industries that should be taken in the Zamrud conservation areas. Results: A number of specific measures were employed by CPI to protect this sensitive area including a green seismic project, zero-discharge drilling, water management, preservation of nature and regular monitoring and impact assessment. There are two important points that should be in consideration for the environmental management system by CPI in the Zamrud areas, including top soil utilization to maintain biological and nutrients quality and re-vegetation in all areas of significant disturbances. Conclusion: oil and gas exploration and production in conservation areas has to be managed through high commitment to good environmental and social practices. Key words : Environmental Management System (EMS), Petroleum Industries, Zamrud Field